METODE PEMBELAJARAN BAHASA INGGRIS DI TINGKAT DAS - M. Yamin (Universitas Syiah Kuala, 2022)
Language learning is a communication skill in various communication contexts. Learning English is essentially learning communication. Therefore, language learning is directed to improve the learner's ability to communicate, whether oral or written. The most basic and most necessary language elements are: vocabulary, pronunciation, simple grammar, and simple conversation. In addition to the elements of the language, one thing that should always be remembered by an English teacher is the importance of creating a comfortable situation and generate interest and motivation to learn English. Therefore, when children learn English from the beginning, they should learn in a pleasant situation by competent teachers, so that it can be a motivation and their capital to learn English at a more advanced level. Some of the relevant English learning methods for basic level are: Total Physical Response (TPR), The Reading Method, Songs and games, dan Field Study.